Hubungan Ketersediaan Media Interaktif Interactive Flat Panel (IFP) Dengan Kemampuan Berpikir Anak Tk Kelompok B Pada Pembelajaran Mendalam - Afkarina, Faizatul; Nasikhah, Ikha Durrotun (AL IHSAN: Jurnal Pendidikan Islam Anak Usia Dini, 2026)
Using technology-based learning media in preschool education is crucial for creating a more interactive and meaningful learning experience. However, learning that still uses old methods often leaves children uninvolved, resulting in underdevelopment of higher-order thinking skills. Therefore, it is necessary to use interactive media that can improve the quality of the learning process. This research aims to understand the relationship between the presence of interactive media in the form of Interactive Flat Panel (IFP) and children's thinking skills in group B in in-depth learning at NU Tsamrotul Afkar Kindergarten. A correlational approach based on quantitative methods was applied in this research, involving the entire population of group B students totaling 15 children, where the census technique (total sampling) was chosen as the sampling method. The independent variable was the presence of IFP measured through observation sheets, while the dependent variable was the children's thinking skills measured through tests and teacher observations. Data analysis was carried out using two approaches, namely descriptive and inferential, which included testing data normality, linearity, and calculating Pearson Product Moment correlation. The study findings indicate a very strong and significant correlation between the availability of IFP and the level of children's thinking ability (r = 0.886; p < 0.001), with an R² value of 0.785. This indicates that 78.5% of the variation in children's thinking ability can be explained by the availability of IFP. These findings indicate that the use of interactive media in in-depth learning has a significant relationship in improving children's thinking ability.